2020
DOI: 10.4049/immunohorizons.1900086
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression through Gut Microbiota-Dependent DNA Methylation in Colonic Epithelial Cells

Abstract: A huge number of commensal bacteria inhabit the intestine, which is equipped with the largest immune system in the body. Recently, the regulation of various physiological functions of the host by these bacteria has attracted attention. In this study, the effects of commensal bacteria on gene expression in colonic epithelial cells (CoECs) were investigated with focus on regulation of DNA methylation. RNA sequencing analyses of CoECs from conventional, germ-free, and MyD88 2/2 mice indicated that, out of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It is a naturally occurring, biologically active metabolite of vitamin A. Retinol is vital to maintaining the integrity of the epithelium and mucous membranes ( 60 ). Previous studies showed that symbiotic bacteria produced retinol derivatives that could protect the intestinal epithelial barrier ( 61 , 62 ). Besides, Goji and its trained microbiota also upregulated the levels of L-glutamic acid and pyroglutamic acid, which are involved in GSH metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is a naturally occurring, biologically active metabolite of vitamin A. Retinol is vital to maintaining the integrity of the epithelium and mucous membranes ( 60 ). Previous studies showed that symbiotic bacteria produced retinol derivatives that could protect the intestinal epithelial barrier ( 61 , 62 ). Besides, Goji and its trained microbiota also upregulated the levels of L-glutamic acid and pyroglutamic acid, which are involved in GSH metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the colon, which has a larger population of commensal bacteria compared to the small intestine, DNA methylation of the TLR4 gene in IECs depends on gut microbiota, indicating that commensal bacteria themselves maintain the symbiotic environment by causing epigenetic changes in host cells (Takahashi et al, 2011). In addition, we observed that the 5′ regions of specific populations of genes whose expression is downregulated by gut microbiota are highly methylated in colonic epithelial cells, suggesting that induction of DNA methylation serves as a mechanism by which the gut microbiota can regulate gene expression in IECs (Takahashi et al, 2020). However, the precise underlying molecular mechanisms remain to be elucidated.…”
Section: Introductionmentioning
confidence: 74%
“…Superficial colonocytes lining intestinal crypts absorb SCFAs as energy and subsequently, impede diffusion to the stem cell niche where stem cell proliferation is suppressed by these metabolites [188]. The interplay between IECs and the microbiota entails the regulation of HDACs and alteration of host epigenome in order to reinforce gene expression and barrier function [189]. Intestinal homeostasis and barrier integrity is sustained when HDAC is expressed in IECs.…”
Section: Microbiota-dependent Regulation Of Epigenomic Pathways In Iecsmentioning
confidence: 99%
“…Histone or nonhistone proteins are cleared of acetyl residues by HDACs. Massive protein complexes are home to such epigenomic-modifying enzymes that are directed towards target chromatin by means of transcription factor interactions [189][190][191].…”
Section: Microbiota-dependent Regulation Of Epigenomic Pathways In Iecsmentioning
confidence: 99%